2014
DOI: 10.14444/1012
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Lumbar Total Disc Replacement: Selecting the Right Patient with the Right Indication for the Right Total Disc

Abstract: Summary of Background DataAs with any surgery, care should be taken to determine patient selection criteria for lumbar TDR based on safety and optimizing outcome. These goals may initially be addressed by analyzing biomechanical implant function and early clinical experience, ongoing evaluation is needed to refine indications.ObjectiveThe purpose of this work was to synthesize information published on general indications for lumbar TDR. A secondary objective was to determine if indications vary for different T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…However, this may lead to eventual adjacent segment degeneration (Ghiselli, Wang, Bhatia, Hsu, & Dawson, ). As modern disk arthroplasties cannot fully imitate the mechanical function of the native joint and can only be performed in a small subset of affected patients (Büttner‐Janz, Guyer, & Ohnmeiss, ), the available treatment options collectively highlight that the field would benefit from a better understanding of the underlying pathophysiology and causally acting interventions (Hanley et al, ). Indeed, first clinical regenerative approaches are emerging (Sakai & Andersson, ; Vadalà, Russo, Ambrosio, Loppini, & Denaro, ), but their long‐term clinical results (Tschugg, Michnacs, Strowitzki, Meisel, & Thomé, ) have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may lead to eventual adjacent segment degeneration (Ghiselli, Wang, Bhatia, Hsu, & Dawson, ). As modern disk arthroplasties cannot fully imitate the mechanical function of the native joint and can only be performed in a small subset of affected patients (Büttner‐Janz, Guyer, & Ohnmeiss, ), the available treatment options collectively highlight that the field would benefit from a better understanding of the underlying pathophysiology and causally acting interventions (Hanley et al, ). Indeed, first clinical regenerative approaches are emerging (Sakai & Andersson, ; Vadalà, Russo, Ambrosio, Loppini, & Denaro, ), but their long‐term clinical results (Tschugg, Michnacs, Strowitzki, Meisel, & Thomé, ) have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the aforementioned points into account, lumbar TDR might be considered a viable treatment option in patients suffering from painful DDD unresponsive to more than 6 months of nonoperative care with diagnostic studies confirming the disc as the likely pain generator, and without significant facet joint degeneration, deformities, instabilities or osteopenia/osteoporosis [26].…”
Section: Selection Criteria For Lumbar Tdrmentioning
confidence: 99%
“…In addition, there are less adjacent‐level effects such as excessive range of motion (ROM), which can cause accelerated degeneration at adjacent level, than with that of conventional fusion methods . The major indication for TDR in the lumbar spine is symptomatic DDD, and various factors such as bone quality and source of pain are examined before the surgery …”
Section: Introductionmentioning
confidence: 99%
“…2,3 The major indication for TDR in the lumbar spine is symptomatic DDD, and various factors such as bone quality and source of pain are examined before the surgery. 4 The condition of facet joints is also an important factor in determining TDR in terms of contraindication: patients who have degenerative facet joints should be excluded from TDR, as the preserved spinal motion can cause adverse effects on the facet joints. Although TDR is limited to patients with DDD without facet joint problems, long-term follow-up clinical studies have reported progressive facet arthrosis as a major complication after TDR.…”
mentioning
confidence: 99%